Pemphigus herpetiformis - a case report of a rare form of pemphigus and review of the literature - Stojković-Filipović Jelena; Lekić Branislav; Milčić Danijela; Milinković Mirjana V. (Vojnosanitetski Pregled)
Introduction. Pemphigus herpetiformis is the rare variant of pemphigus with characteristic clinical features, histopathological findings different from the convectional pemphigus, and immunological findings consistent with pemphigus. Case report. We presented a 65-year-old woman with initial pruritus followed by pruritic urticarial papules and plaques, some with annular rings of tense vesicles on the periphery, on the trunk and extremities, with no mucous lesions. Histopathological examination demonstrated spongiosis and intraepidermal vesicles in the mid or subcorneal epidermis in some biopsy specimen, with neutrophil and eosinophil infiltrate. Direct immunoflorescent microscopy revealed intercellular IgG deposition, most prominent in the upper layers of epidermis. Indirect immunoflorescent microscopy showed intercellular binding of IgG autoantibodies in the patient’s sera. Initially the patient was threated with systemic corticosteroids and azathioprine, but dapson provided complete clinical remission. Conclusion. This entity was established 40 years ago, and around 100 patients have been reported worldwide. It is important to be aware of this particular form of pemphigus because clinical presentation, course of the disease and therapeutic approach are different from conventional forms of pemphigus.